Konzeptionelle Untersuchung zur Neigekompensation von Stromabnehmern - Kölling, Steffen (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2015)
Interoperability of pantographs is being limited by different pantograph head profiles in the European rail networks. In this regard, the researched aspect leads to the question if a smaller pantograph head can be used in a network with originary wider head widths. The other part is focused on the technical realization of the swing compensation for pantographs mounted on tilting trains.